Social Entrepreneurs' Experiences of Ethical Dilemmas : An Interpretative Phenomenological Analysis - Slunga, Ella (2023)
The dominant narrative in social entrepreneurship posits it being inherently ethical; however, this study challenges this assumption by exploring social entrepreneurs’ experiences of ethical dilemmas. The study aims to provide a deeper understanding of the complexities of ethics in the field of social entrepreneurship and sheds light on the individuality of social entrepreneurs' ethical decision-making processes, their awareness, emotional and cognitive responses, and sensemaking activities. Employing Interpretative Phenomenological Analysis, this research investigates how social entrepreneurs experience ethical dilemmas, examines their perceptions and sensemaking of these experiences, and explores the role of ethical dilemmas in social entrepreneurship. Phenomenological interviews were conducted with nine purposefully chosen social entrepreneurs involved in startups or small-to-medium sized social ventures based in Finland. The analysis reveals five main themes of ethical dilemmas: ethical decision-making, balancing social impact and financial sustainability, navigating systemic and institutional constraints, community engagement, and overcoming personal barriers. By challenging the prevailing notion of social entrepreneurship's inherent ethicality, the findings contribute to a more nuanced understanding of ethics in the context of social entrepreneurship. This study informs the development of ethical practices in social entrepreneurship and enhances knowledge of the field. The practical implications and recommendations derived from this study offer valuable guidance on leveraging ethical dilemmas in social entrepreneurship endeavors.